Kompleksitas Tugas, Audit Fee, dan Kualitas Audit: Moderasi Diskriminasi Harga - Jessica Regata Melanie; Dewi Darmastuti (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: This study aims to examine the effect of task complexity and audit fees on audit quality and examine the moderating effect of price discrimination based on KAP's reputation on this relationship.Method: This study used Structural Equation Modeling (SEM) analysis of 117 questionnaires obtained from a survey conducted on auditors at PAF in DKI Jakarta.Results: The results of this study indicate that task complexity has a negative effect on audit quality. Price discrimination weaken the effect of task complexity on audit quality. Meanwhile, audit fees have no effect on audit quality. There is a direct effect of price discrimination on audit quality.Implications: This study result have implications for the compliance theory implementation. Audit complexity and audit fees can motivate auditors to produce good quality audit reports because auditors must be professional and comply with the code of ethics.Novelty: This study adds moderation of price discrimination based on KAP's reputation which is rarely researched in Indonesia. This study provides input for policy formulation for equal opportunity for local KAPs to acquire clients so as to minimize price discrimination based on KAP reputation.Â